Outcome predictors of co-operative R & D in Europe: organisational capabilities and cultures - Zibell, Laurent (Cranfield University, 2010)
This research investigates organisational capabilities and cultures of both partners as potential explanatory factors of co-operative R&D projects outcomes. Contributions to theory are (1) a justification for the existence of organisational capabilities and 'world views', (2) a parsimonious typology of 'world views' and (3) a method to measure organisational capabilities. The survey covers 514 projects in the electronics industry, in Germany, France, the United Kingdom and Finland. It obtains 120 full answers, each of which coupling responses from a matched pair of project managers having co-operated on the same R&D project. The survey refers to the organisation's capabilities, to those of the partner, to its 'world view', and to project outcomes. None of the traditional explanatory factors (geographic distance, difference in nationality, size or legal status, strategic compatibility) has any significant influence on any of the outcomes being studied (save one). The explanatory factors introduced by the research (organisational capabilities and 'world views') have a significant influence on almost all outcomes being considered of the co-operative R&D projects: attainment of concrete results, compliance with budget and schedule, creation and transfer of knowledge, learning (modification of capabilities). Cultural diversity, 'absorptive capacity', and teaching effects, selective according to the capability in question, are evidenced. Commonalities between partners are shown to be more important than distance. These results validate empirically organisational capabilities and 'world views' as descriptors of inter-organisational capabilities, and their operationalisation.
Keywords: Cognitive distance; Collective competence; Cooperation; Dyad; Electronics industry; Europe; Finland; France; Germany; Innovation; Organizational capability; Organizational culture; Project; R&D; United Kingdom; World view